Ginsenoside Contents in Ginseng: Quality by Design-Coupled Two-Dimensional Liquid Chromatography Technique. (19th May 2021) - Yang, Yuangui; Zhang, Yanhai; Zhang, Xiaoqun; Yang, Li; Wang, Zhengtao
Abstract: Red ginseng and white ginseng, with different chemical constituents, exhibit different antioxidative, anticancer, antiasthmatic and immunomodulatory properties. The aim of this study was to determine the amount of ginsenoside contents (Rg1, Re, Rb1, Rb2, Rc, Rd and Ro) in red and white ginseng. A rapid and comprehensive method was developed using the quality-by-design (QbD) and heart-cutting two-dimensional liquid chromatography (2D-LC) techniques. The temperature (25°C), mobile phase constituent (0.1%H3 PO4 ), flow rate (0.35 mL/min) and concentrations of the final (45%) and initial (19.5%) organic solvents were optimized to efficient chromatography-based isolation method. The gradient program was optimized by QbD Fusion AE system. A selective column (Thermo Acclaim RSLC Polar Advantage II 2.2 μm, 100 × 2.1 mm) was used for the studies. The ginsenoside Rb1, Rc and Ro exhibiting poor separation resolution were separated using the heart-cutting 2D-LC technique. The average Rb1, Rb2 and Rc contents in red ginseng were significantly higher than the average Rb1, Rb2 and Rc contents in white ginseng. Ginsenoside Ro can be potentially used as a marker to evaluate the qualities of white and red ginseng. This comprehensive and rapid method can be potentially used to screen the quality of the markers in the future.